PERSONAL BRANDING GANJAR PRANOWO DI MEDIA SOSIAL - Anggita Muti Arani Zulaikho; Joyo Nur Suryanto Gono; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Current competitive conditions and developments force every political candidate to think about the right way and method to win the competition. Personal branding is one of the methods that can be used and it is something that cannot be avoided by every candidate who enters politics. The presence of the Internet has given rise to a type of social media that has become an opportunity to build personal branding. Ganjar Pranowo is a political figure who uses social media to build trust and image, as well as build personal branding. Through his Instagram account @ganjar_pranowo, Ganjar Pranowo has succeeded in displaying a positive personal branding impression, thus influencing his image in the public eye. The method in this research is a qualitative method with a descriptive approach. This study uses semiotic analysis developed by Ferdinand De Saussure as its basis. The data collection techniques used are observation and documentation. Data analysis used data reduction, data presentation, and drawing conclusions by analyzing existing data based on the theory used in this research. From the research that has been conducted on the @ganjar_pranowo Instagram account, it shows that the personal branding displayed by Ganjar Pranowo fulfills the eight concepts of forming personal branding from Peter Montoya, namely the law of specialization, the law of leadership, the law of personality, the law of distinctiveness, the law of visibility, the law of unity, the law of persistence, and the law of goodwill. Then, the personal branding displayed by Ganjar Pranowo through his Instagram account can also be analyzed using Erving Goffman's Dramaturgy Theory which consists of front stage and back stage. Ganjar Pranowo in uploading posts on Instagram as an effort to build personal branding uses features from Instagram in the form of feeds, captions, reels, and highlights.